2017
DOI: 10.1002/14651858.cd009758.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for the prevention of recurrent erysipelas and cellulitis

Abstract: Cochrane Database of Systematic Reviews penicillin and one erythromycin), which was compared to either no treatment or placebo, and one trial used selenium compared to physiological salt solution. Treatments lasted from six to 18 months.The most common setting was the hospital, and two studies were multicentre. The studies were conducted in the UK, Sweden, Tunisia, Israel, and Austria. There was a small number of previous episodes of cellulitis in those recruited to the trials, ranging between one and four epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 133 publications
1
55
0
4
Order By: Relevance
“…[8] Risk factor modification including treatment of lymphedema and tinea pedis is also recommended for reduction of cellulitis recurrence. [22]…”
Section: Discussionmentioning
confidence: 99%
“…[8] Risk factor modification including treatment of lymphedema and tinea pedis is also recommended for reduction of cellulitis recurrence. [22]…”
Section: Discussionmentioning
confidence: 99%
“…Prophylaxie secondaire: traitementd'uneported'entrée persistante (antifongique topique encas d'intertrig omycosique) [2], prise en charge des facteurs favorisants (insuffisance veinolymphatique, obésité, etc.). En cas de récidives multiples, une antibiothérapie au long cours possible [6].…”
Section: Discussionunclassified
“…This review included all RCTs that were included in two Cochrane reviews: ‘interventions for the prevention of recurrent erysipelas and cellulitisʼ, published in June 2017, and the Cochrane update: ‘interventions for the treatment of cellulitis and erysipelas’ (awaiting publication but obtained from personal communication with the authors). Studies that assessed treatment or prevention of cellulitis, erysipelas or skin and soft‐tissue infection were included in this review.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the impact of the disease, there are few well‐conducted trials looking into the treatment and prevention of cellulitis . It has been reported that clinical assessment of cellulitis many not capture the patient's experience, and may be unreliable in reflecting real effects for patients …”
mentioning
confidence: 99%